MATHEMATICAL CRITICAL THINKING ABILITY BASED ON STUDENT’S SELF-EFFICACY USING PHENOMENOLOGICAL STUDY APPROACH - Irfa Ul Umam; Elah Nurlaelah; Suhendra Suhendra (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2023)
Critical thinking is a key skill in terms of being used in most thinking processes. There is one variable related to critical thinking, namely self-efficacy. This can be seen from a positive significant relationship between self-efficacy and critical thinking. In this regard, this study aims to describe mathematical critical thinking abilities based on students' self-efficacy. This study uses a phenomenological approach. The researcher gave a self-efficacy questionnaire to class X students at a public high school in the city of Bandung, followed by giving tests on critical thinking skills, and conducted interviews with students with high self-efficacy (ST), medium self-efficacy (SS), and low self-efficacy (SR). The results show that ST belongs to high-level mathematical critical thinking skills in solving math problems. If students have high self-efficacy, so it will also have an impact on high critical thinking skills. SS is in the category of moderate-level critical thinking skills, thus showing that students with moderate self-efficacy do not necessarily have moderate-level mathematical critical thinking skills. SR cannot solve the given questions correctly and completely, so students with low levels of self-efficacy have low mathematical critical thinking skills.